2012
DOI: 10.2345/0899-8205-46.6.470
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram Interference: A Thing of the Past?

Abstract: This paper focuses on the problem of high and/or imbalanced electrode-skin impedances changing electrocardiogram (ECG) morphology. After reproducing ECG interference in a controlled laboratory setting-similar to what was observed during cardiopulmonary bypass surgery- and then understanding the cause, this knowledge was applied to clinical settings. Most interference was reduced by using electrode impedance meters and consistent skin prep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…435,447 Alcohol should not be used because it dries the skin and may diminish electric flow. 447 Melendez and Pino 446 showed that interference was reduced with proper skin preparation as one of their interventions. However, they did not specifically identify their mode of skin preparation.…”
Section: Skin Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…435,447 Alcohol should not be used because it dries the skin and may diminish electric flow. 447 Melendez and Pino 446 showed that interference was reduced with proper skin preparation as one of their interventions. However, they did not specifically identify their mode of skin preparation.…”
Section: Skin Preparationmentioning
confidence: 99%
“…444,445 The purpose of skin preparation is to cleanse the area to optimize signal transfer. Research, 446 QI projects, 435,437 and expert opinion 445,447 have identified proper skin preparation before electrocardiographic electrode ap plication to optimize conductivity. The skin is prepared by cleansing the area and wiping it with a dry wash cloth.…”
Section: Skin Preparationmentioning
confidence: 99%
“…Good skin preparation decreased impedance, which in turn resulted in less ECG interference. 49 Although there is evidence to support proper skin preparation on individuals, only 1 study examined its effect on telemetry patients. Cvach 20 examined the effect of daily electrode change using proper skin preparation on a medical progressive care unit for 8 days before and after a daily electrode change policy was implemented.…”
Section: Literature Reviewmentioning
confidence: 99%